Experiences and Perceptions of Police Officers Concerning Their Interactions With People With Serious Mental Disorders for Compulsory Treatment - Soares, Ruben; Pinto da Costa, Mariana (Frontiers in Psychiatry, 2019)
Background: In Portuguese law, police officers are the link between security and the treatment of people with serious mental disorders who require compulsory admission. The perceptions of police officers are in part based on their individual characteristics, and may influence their capability in managing patients they are transporting. However, little is known about police officers experience of this process. Methods: In-depth semi-structured interviews explored the experiences and perceptions of police officers from Porto Police Department in Portugal. All interviews were audio recorded, transcribed and analysed through thematic analysis. Results: Ten police officers agreed to take part in this study. The interviewed police officers consisted of nine men and one woman, had an average length service of 22.6 years and all had more than 10 years of service. The interviews highlighted that the activity of the police under the Mental Health Law is shaped by whether the person who they are transporting has a mental health disorder and requires psychiatric admission. The police officers reportedly adjusted their behaviour to give patients more attention, comfort and empathy. However, they describe these interactions as one of the most time consuming and challenging activities for the police. Importantly, they acknowledged family members as crucial for police officers to be able to gain direct access to patients and knowledge about them. Police officers showed to perceive people with mental illness as unpredictable, dangerous and without discernment, and identified some aspects of the process that could be improved, such as hospital admission waiting times. Police officers felt they required more skilled support to deal with unwell patients. Conclusions: This study highlights the perceptions and experiences of police officers about the process of compulsory admission, and identifies areas of unmet needs. These findings help to raise awareness of their needs, improving this process, and ensuring a more humane and effective approach.